Quality of life in patients after glossectomy: systematic review (Research, Society and Development, 2020)
Objective: To present scientific evidence based on a systematic review of the literature on the quality of life of post-glossectomy patients through a systematic review. Methodology: Search performed in the electronic databases Medline (Pubmed), LILACS, SciELO, ScienceDirect, SCOPUS and Google Scholar (gray), without restriction of languages and location, research period from January 2010 to August 2020. Results: 101 articles were retrieved in primary searches and after all phases of exclusion following the PRISMA criteria, two articles met the inclusion criteria and were admitted for this study. Conclusion: It is evident that the surgical process results in the loss of some oral functions, which directly reflects on the quality of life of patients, mainly affecting the functions of chewing and swallowing. In addition to resection surgery that will affect the mobility of the tongue, when treatment is associated with radiotherapy, it will have other consequences such as xerostomia that hinder the practice of proper swallowing, directly impacting the quality of life of individuals.